Pembacaan Makna Nusyūz Dalam Tafsir Jami’ Al-Bayan Dan Al-Qur’an Al-Azhim - Muhaini Hidayatullah; Siti Asiah (STAI Darul Kamal NW Kembang Kerang, 2022)
This research is an attempt to find out how At-Tabari and Ibn Kathir's views on nusyūz. This started from the many understandings circulating in the community that the problem of nusyūz was only shown and questioned to women (wives). The understanding that tends to be textual in Surah An-Nisa verse 34 is often used as an excuse as an excuse to commit acts of violence against women, both physically and psychologically. While the reading in another verse, namely in Surah An-Nisa verse 128 shows that husbands can also do nusyūz. From this study, it shows that At-Tabari in the book Jami' Al-Bayan and Ibn Kathir in Tafsir Al-Qur'an Al-Azhim argues that either wife or husband nusyz is a form of hatred for a partner and leaves the obligations that have been set in domestic life. , and the completion of the wife's nusyūz is that there are three stages, namely advising, separating beds and hitting. while the settlement of husband's nusyz is by peace, then it is necessary to re-read the nusyz concept referred to by using the theory of gender equality in order to find an impartial understanding.